Unusual stability of recombination intermediates made by Escherichia coli RecA protein. - Müller, B (1992)
The structure and stability of recombination intermediates made by RecA protein have been investigated following deproteinization. The intermediates consist of two duplex DNA molecules connected by a junction, as visualized by electron microscopy. Although we expected the structures to be highly unstable due to branch migration of the junction, this was not the case. Instead, we found that the intermediates were stable at 37 degrees C. At 56 degrees C, greater than 60% of the intermediates remained after 6 h of incubation. Only at higher temperatures was significant branch migration observed. This unexpected stability suggests that the formation of extensive lengths of heteroduplex DNA in Escherichia coli is likely to require the continued action of proteins, and does not occur via spontaneous branch migration. We show that heteroduplex DNA may be formed in vitro by ATP-dependent strand exchange catalysed by RecA protein or by the RuvA and RuvB proteins of E. coli.